The serendipitous origin of chordate secretin peptide family members - Cardoso, João CR (2010)
Background: The secretin family is a pleotropic group of brain-gut peptides with affinity for class 2 G-protein coupled receptors (secretin family GPCRs) proposed to have emerged early in the metazoan radiation via gene or genome duplications. In human, 10 members exist and sequence and functional homologues and ligand-receptor pairs have been characterised in representatives of most vertebrate classes. Secretin-like family GPCR homologues have also been isolated in non-vertebrate genomes however their corresponding ligands have not been convincingly identified and their evolution remains enigmatic. Results: In silico sequence comparisons failed to retrieve a non-vertebrate (porifera, cnidaria, protostome and early deuterostome) secretin family homologue. In contrast, secretin family members were identified in lamprey, several teleosts and tetrapods and comparative studies revealed that sequence and structure is in general maintained. Sequence comparisons and phylogenetic analysis revealed that PACAP, VIP and GCG are the most highly conserved members and two major peptide subfamilies exist; i) PACAP-like which includes PACAP, PRP, VIP, PH, GHRH, SCT and ii) GCG-like which includes GCG, GLP1, GLP2 and GIP. Conserved regions flanking secretin family members were established by comparative analysis of the Takifugu, Xenopus, chicken and human genomes and gene homologues were identified in nematode, Drosophila and Ciona genomes but no gene linkage occurred. However, in Drosophila and nematode genes which flank vertebrate secretin family members were identified in the same chromosome. Conclusions: Receptors of the secretin-like family GPCRs are present in protostomes but no sequence homologues of the vertebrate cognate ligands have been identified. It has not been possible to determine when the ligands evolved but it seems likely that it was after the protostome-deuterostome divergence from an exon that was part of an existing gene or gene fragment by rounds of gene/genome duplication. The duplicate exon under different evolutionary pressures originated the chordate PACAP-like and GCG-like subfamily groups. This event occurred after the emergence of the metazoan secretin GPCRs and led to the establishment of novel peptide-receptor interactions that contributed to the generation of novel physiological functions in the chordate lineage.